2020
DOI: 10.26717/bjstr.2020.32.005232
|View full text |Cite
|
Sign up to set email alerts
|

Oral Cancer Senario in Multiple Centers of Dhaka, Bangladesh

Abstract: Oral cancer is one of the common cancers worldwide and in Bangladesh around 7000 cases are diagnosed yearly. It has variable demographics and patient comes to hospital with different presentations. It is mandatory to know the characteristics of the disease so that better awareness and different treatment modalities can be planned. 162 patients with histopathological diagnosis of oral cancer was include in study by consecutive sampling and characteristics of disease was recorded in scientific data collection sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
2
1
1
Order By: Relevance
“…(5) In our study period from January 2017 to December 2020, we observed female predominance which is similar to studies conducted in India and Turkey (8) (12,13). Buccal mucosa (44%) was the most common site followed by lower gingivo-buccal sulcus (21%) in this study which is similar to a study conducted by Rahman et al, and also some Indian and Sri-Lankan Studies (6,1,10,14) This is due to the fact that most of the patients keep tobacco in the form of quid in the buccal sulcus. It is also a true fact for Bangladesh that tobacco and its related products are available at an affordable cost making it a habit for many rural people.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…(5) In our study period from January 2017 to December 2020, we observed female predominance which is similar to studies conducted in India and Turkey (8) (12,13). Buccal mucosa (44%) was the most common site followed by lower gingivo-buccal sulcus (21%) in this study which is similar to a study conducted by Rahman et al, and also some Indian and Sri-Lankan Studies (6,1,10,14) This is due to the fact that most of the patients keep tobacco in the form of quid in the buccal sulcus. It is also a true fact for Bangladesh that tobacco and its related products are available at an affordable cost making it a habit for many rural people.…”
Section: Discussionsupporting
confidence: 89%
“…These two divisions are densely populated and people move here from other locations for job and business purposes. We found oral squamous cell carcinoma, salivary gland malignancy, verrucous carcinoma, and malignant melanoma with other non-squamous cell carcinoma cases 88%, 4%, and 8% respectively, which is similar to a study conducted by Anis and Gaballah (6) Among the preoperative patients, only 29% were operable and 71% were inoperable. This is due to the late presentation of diseases with massive involvement of hard and soft tissues.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations